Analysis and dissociation of anti‐HIV effects of shRNA to CCR5 and the fusion inhibitor C46. (25th March 2018) - Ledger, Scott; Howe, Annett; Turville, Stuart; Aggarwal, Anupriya; Savkovic, Borislav; Ong, Andrew; Wolstein, Orit; Boyd, Maureen; Millington, Michelle; Gorry, Paul R.; Murray, John M.; Symonds, Geoff
Abstract: Background: The gene therapeutic Cal‐1 comprises the anti‐HIV agents: (i) sh5, a short hairpin RNA to CCR5 that down‐regulates CCR5 expression and (ii) maC46 (C46), a peptide that inhibits viral fusion with the cell membrane. These constructs were assessed for inhibition of viral replication and selective cell expansion in a number of settings. Methods: HIV replication, selective outgrowth and cell surface viral binding were analysed with a single cycle infection assay of six pseudotyped HIV strains and a static and longitudinal passaging of MOLT4/CCR5 cells with HIV. Pronase digestion of surface virus and fluorescence microscopy assessed interactions between HIV virions and transduced cells. Results: Cal‐1 reduced CCR5 expression in peripheral blood mononuclear cells to CCR5Δ32 heterozygote levels. Even low level transduction resulted in significant preferential expansion in MOLT4/CCR5 gene‐containing cells over a 3‐week HIV challenge regardless of viral suppression [12.5% to 47.0% (C46), 46.7% (sh5), 62.2% (Dual), respectively]. The sh5 and Dual constructs at > 95% transduction also significantly suppressed virus to day 12 in the passage assay and all constructs, at varying percentage transduction inhibited virus in static culture. No escape mutations were present through 9 weeks of challenge. The Dual construct significantly suppressed infection by a panel of CCR5‐using viruses, with its efficacy being independently determined from the single constructs. Dual and sh5 inhibited virion internalisation, as determined via pronase digestion of surface bound virus, by 70% compared to 13% for C46. Conclusions: The use of two anti‐HIV genes allows optimal preferential survival and inhibition of HIV replication, with the impact on viral load being dependent on the percentage of gene marked cells.